IMPLANTS AND INJECTIONS ARE FAVORITE CONTRACEPTION TOOLS IN SUMATERA SELATAN (Jurnal kesehatan komunitas (Journal of community health), 2019)
Background: The choice of contraception by family planning acceptors greatly determines the success rate of the family planning program, because not all contraceptives are suitable for someone. This study aims to determine what types of contraceptives chosen by family planning acceptors and whether there is a relationship between the selection of contraceptives there is a relationship with the poverty level in the District / City in South Sumatra in 2015, 2016 and 2017. The source of data obtained from the Provincial BPS South Sumatra. Methodology: This study uses a descriptive approach with a simple linear regression analysis method. Results: The results of the analysis were grouped into two, first long-term contraception method KB IUD, MOW, MOP and implants, both short-term contraceptive methods namely injection KB, pill and condom from 17 regencies / cities in South Sumatra. Conclusion: contraception devices that are mostly chosen by long-term contraceptive methods are implants (10000-35000) or 10-20 times larger than other contraceptives. Short-term contraceptive methods are injections, (7700 - 76000) or 5-7 times greater than other contraceptives. From the simple linear regression analysis it turns out that the relationship of long-term contraceptive selection by acceptors with the poverty level is RÂ² = 0.7382 and the short-term method RÂ² = 0.9223. District / City Governments in South Sumatra should provide alokon (contraceptive devices and drugs) in accordance with the type and amount in the field to be on target.